UPAYA MENINGKATKAN LISTENING SKILL PADA PEMBELAJARAN TRANSAKSIONAL TEKS MELALUI METODE THREE PHASE TECHNIQUE DI KELAS VIII - Astati, Era (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Learning English listening for junior high school students is highly recommended so that students are able to communicate verbally. One method that can be used in learning to improve students' listening skills is the Three-Phase Technique Learning Method. The Three-Phase Technique Learning Method is a technique that divides learning activities into three main parts, namely initial activities (Pre Activities), core activities (Main Activities), and final activities (Post Activities). This study focuses on improving abilities, namely listening skills. This study is a type of classroom action research (PTK) through the stages of planning, implementation, evaluation and reflection for two cycles. The results of this PTK concluded that there was an increase in students' listening skills after going through transactional text learning using the Three-Phase Technique Learning Method. In the pre-cycle, the achievement of learning completeness was 37.5%, cycle I was 65.6% and in cycle II it reached 84.3%. With the indicator of the achievement of this PTK success, the learning completeness was at least 80%, so this PTK has been successfully and effectively implemented for two cycles. ABSTRAKBelajar listening Bahasa Inggrispada siswa SMP sangat dianjurkan agar siswa mampu berkomunikasi secara verbal. Salah satu metode yang bisa digunakan dalam pembelajaran untuk meningkatkan aspek listening skill siswa adalah Metode Pembelajaran Three-Phase Technique. Metode Pembelajaran Three-Phase Technique adalah teknik yang membagi kegiatan pembelajaran menjadi tiga bagian utama yaitu kegiatan awal (Pre Activities), kegiatan inti (Main Activities), dan kegiatan akhir (Post Activities). Dalam penelitian ini memfokuskan pada peningkatan kemampuan yaitu kemampuan listening skill. Penelitian ini berjenis penelitian tindakan kelas (PTK) melalui tahapan perencanaan, pelaksanaan, evaluasi dan refleksi selama dua siklus. Hasil PTK ini diperoleh simpulan bahwa adanya peningkatan listening skill siswa setelah melalui pembelajaran transaksional teks menggunakan Metode Pembelajaran Three-Phase Technique. Pada pra siklus, capaian ketuntasan pembelajaran sebesar 37,5%, siklus I sebesar 65,6% dan pada siklus II mencapai 84,3%. Dengan indikator capaian keberhasilan PTK ini ketuntasan pembelajaran minimal 80% maka PTK ini telah berhasil dan efektif diterapkan selama dua siklus.